(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The purpose of this study is to identify the problems educational counselor have while applying the case study approach. In general, and to identify the difference between them according to the gender variable (male - female), the researcher has built the scale of problems (2022) facing the educational counselor and before using the scale, its psychometric characteristics necessary and necessary to apply it to the research sample were ascertained. The research sample comprised (60) male and female school counsellors from public schools affiliated with the Department of Education Nasiriyah and the General Directorate-General for Education Thi Qar. To achieve the purpose of the study, the researcher employed the descriptive research method to collect, analyse, and interpret the results; the questionnaire served as a research instrument and a way to achieve the purpose. After assessing the sample members’ questionnaires using the mean and equation of the T test for two independent samples. The most crucial finding of the study is the lack of awareness regarding the function of Rashad in education and the magnitude of its impact on society in general and the school in particular, the research concluded that the level of problems encountered by educational counsellors as a result of the implementation of the case study is more than the scale’s mean score and that there are no statistically significant gender differences. There is a weakness in the relationship between the educational counselor and the parents of the students, and also the lack of allocation of a room for the educational counselor prevents him from performing his assigned work, in addition to the lack of interaction between the educational counselor and the teaching staff. It may appear that these problems have a significant impact on the functioning of the educational counsellor, given that they play a significant role in reducing or removing the presence of the educational counsellor. In addition, there were no statistically significant differences based on the gender variable.